Cohesiveness in Expository Writing by Saudi EFL Students - Hani, Al Amri (Advances in Social Sciences Research Journal, 2023)
This research aimed to examine cohesive connectivity in expository writing by language and translation students at the University of Tabuk in Saudi Arabia. Halliday and Hasan’s (1976) list of cohesive devices was used to examine the cohesion of expository texts of language and translation students. The study examined the cohesive devices’ quality and their contribution to the quality of writing. This mixed-mode research included 34 participants. 30 undergraduates participated in the expository writing assignment and 4 EFL teachers participated in the semi-structured interview. Students were selected purposively. Expository written texts were the instrument used to collect data in this study. Results showed that students encountered cohesion and coherence problems in achieving written texts’ unity, particularly in assigning their concepts and implementing appropriate cohesive signals, punctuation, and spelling issues. Expository texts were examined for cohesion additives, adversatives, and causal and temporal devices. Results of the study showed that the existence and unnecessary occurrence of lexical items cause non-cohesive writing and influence its texts’ quality, meaning, structure, and unity. The researcher recommends as related to the results of the study that cohesion devices be incorporated into the teaching of writing.